Licensing of Orphan Medicinal Products—Use of Real-World Data and Other External Data on Efficacy Aspects in Marketing Authorization Applications Concluded at the European Medicines Agency Between 2019 and 2021 - Naumann-Winter, Frauke; Wolter, Franziska; Hermes, Ulrike; Malikova, Eva; Lilienthal, Nils; Meier, Tania; Kalland, Maria Elisabeth; Magrelli, Armando (Frontiers in Pharmacology, 2022)
Background: Reference to so-called real-world data is commonly reported in marketing authorization applications (MAA) for medicines to treat rare diseases. We provide granularity on type and aim of external data on efficacy aspects by quantifying its contribution according to various regulatory characteristics. Methods: Information on external data in regulatory documents covering 72 orphan designations was extracted. Our samples consisted of public assessment reports for approved, refused, or withdrawn applications concluded between 2019-2021 at the European Medicines Agency. Products with an active orphan designation at the time of submission were scrutinized regarding the role of external data on efficacy aspects in the context of MAA, or on the criterion of “significant benefit” for the confirmation of the orphan designation at the time of licensing. The reports allowed a broad distinction between clinical development, regulatory decision-making and intended post-approval data collection. We defined three categories of external data: administrative data, structured clinical data, and external trial data and noted whether external data concerned the therapeutic context of the disease or the product under review. Results: Reference to external data with respect to efficacy aspects was included in 63% of the approved medicinal products. Purely administrative data did not play any role in our sample, but clinical data collected in a structured manner were used to inform on trial design. Two additional recurrent themes for the use of external data were contextualization of results and reassurance of transformational benefit or consistency of effects. External data on the product under review was restricted to either active substances already belonging to standard of care, or to compassionate use schemes. Furthermore, external data was considered pivotal for MA only exceptionally. Applications for the rarest conditions and those without treatment alternatives were especially prominent with respect to use of external data from real-world data sources both in the pre- and post-approval setting. Conclusion: Specific opportunities for external data in the setting of marketing authorizations in the field of rare diseases were identified. Ongoing initiatives of fostering systematic data collection are promising steps for a more efficient medicinal product development in the field of rare diseases.